Education Policies in the 21st Century Comparative Perspectives - Akgün, Birol; Alpaydın, Yusuf (Maarif Global Education Series, 2022)
This open access book explores the agenda of education policies in the 21st century. In the first part of the book, education is handled from a historical and political framework, and the effects of the change of states and policies on education are examined. In the second part, the effects of changes in the economy on education policies and economies' demands from educational institutions are examined. In the last section, current policies in the international education sector, which is growing day by day as a result of increasing globalization and internationalization, are examined and future trends are tried to be revealed. In articles written by academics from different universities all over the world, the topics are presented in a comparative perspective.